Pemberdayaan Kelompok Wanita Tani “Maju Bersama” melalui Diversifikasi Produk Pangan Lokal di Desa Kembang Kerang - Dwi Haryati Ningsih; Fedya Diajeng Aryani; Siti Reuni Inayati (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
This community service program aims to empower the Maju Bersama Women Farmers Group (KWT) in Kembang Kerang Village through diversification of local food products based on tubers, especially cassava. The main problems faced by partners are limited production technology which still uses manual tools, minimal knowledge regarding post-harvest processing, and limited marketing strategies which are still simple. The methods used include socialization, Focus Group Discussions (FGD), training in food processing such as cassava chips and tape cake, and marketing management training based on the 4P mix (product, price, place, promotion). The results of the activity showed a significant increase in the skills of KWT members in production and marketing, as evidenced by an increase in cassava chip production capacity to 25 kg per day, a 25% increase in sales compared to the previous day, and 100% understanding of KWT members regarding product marketing aspects. The application of appropriate technology in the form of chip cutting machines and ovens also had an impact on increasing the quality, quantity, and selling value of the product. Thus, this activity has proven effective in strengthening the economic independence of farming households and contributing to strengthening local food security.